Production and characterization of bio oil from wood sawdust via fast pyrolysis - Sandra Diana, Md Zin (2010)
In this study, the production and characterization of bio oil from wood sawdust via fast pyrolysis was investigated. In fast pyrolysis of wood sawdust, the yields of the products were studied to elucidate the effect of the process parameters such as pyrolysis temperatures, nitrogen (N 2) gas flow rate and pyrolysis holding time. This research was carried out in a design electric furnace reactor and heated externally. The yields product from this experiment were collected and analyzed. The experiments were conducted at a temperature range of 450-550 ⁰C. The holding time was varied in the range 1-5 minutes, and the nitrogen (N2) gas flow rate was varied in the range of 1-3 liter/min. The general characteristic of the product was investigated by the determination of the functional groups present in the bio oil using Fourier Transform Spectroscopy (FTIR). The best conditions to produce bio oil from various parameters that give the highest product yield were at temperature 500 ⁰C, 1 minute of holding time and 3 liter/min of nitrogen (N2) gas flow rate. The maximum yield of bio oil produced from these conditions was 44.6%. From the analysis, it was shown that the pyrolysis oils contain complex compounds mostly functional groups of phenol, alcohols, ketones, aldehydes and carboxylic acids aromatic and also carbonyl structures.